The Role of Photoprotection in Optimizing the Treatment of Atopic Dermatitis - Piquero-Casals, Jaime (Dermatol Ther (Heidelb), 2021)
Atopic dermatitis (AD) is a chronic inflammatory skin disease with an estimated prevalence of 10–15% in children and 2–10% in adults. Clinically, there is notable phenotypic variability driven by a complex interaction between genetics, immune function, and the environment. Impairment of the skin barrier plays a significant role in the pathogenesis of AD. The apparent beneficial effect of sunlight in patients with atopic eczema is questioned due to its capacity to disrupt the skin barrier and generate free radicals that can damage proteins, lipids, and DNA. The sum of the external factors that an individual is exposed to throughout their lifetime is termed the exposome. Environmental factors such as sun exposure, temperature, and humidity contribute to both AD flares and regional prevalence variation. Literature on photoprotection in atopic dermatitis is very scarce. The use of adequate sunscreens in atopic dermatitis can ensure the level of photoprotection required to prevent skin photoaging and skin cancer and to mitigate skin barrier dysfunction, decrease inflammation, and neutralize facial redness. Herein we discuss and review the role of UV radiation and the exposome in the etiology of AD, as well as the role of adequate photoprotection.